PENGARUH SISTEM PENILAIAN KINERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Eli Retnowati; Arif Rachman Putra (Universitas Mahendradatta Denpasar, 2023)
Analysis of the intention to change jobs carried out by employees in an organization based on performance appraisal systems and job satisfaction is the goal of this study. There are several factors that play a significant role in influencing employee retention and organizational stability. That factor is the performance appraisal system and job satisfaction. Understanding the relationship between these factors can assist organizations in designing effective human resource management strategies. Researchers chose a survey method with a quantitative approach. The technique of obtaining the sample in this study was carried out randomly based on various departments in the related organization. The data collection uses a specially designed questionnaire so that the involvement of the performance appraisal system variables, job satisfaction and turnover intention can be measured. Statistical software can help to analyze the data which uses multiple regression analysis. This study found that the performance appraisal system has a significant and negative effect on turnover intention. This shows that the better the performance appraisal system implemented in the organization, the lower the employee's intention to change jobs. In addition, the negative and significant effect of job satisfaction is real on turnover intention. Jobs that can provide a sense of satisfaction for employees, the intention to change jobs is also lower. Through this research, for organizations the factors that influence turnover intention can be better understood. These findings can be used by organizations to improve performance appraisal systems and improve the factors that affect job satisfaction so as to reduce employee turnover rates